Information Technology - Curriculum for Library and Information Science Course at INSDOC, New Delhi - Sen, B. K. (Journal of Information and Knowledge, 2014)
Discusses various information technologies that have been emerging during the last three deeades. Identifies their role in the design and development of information products and services. Provides a guideline on selecting the appropriate aspects of information technology in Library and Information Science curriculum. Provides the curriculum structure adopted for Information technology course in INSDOC.